2015
DOI: 10.15171/hpp.2015.028
|View full text |Cite
|
Sign up to set email alerts
|

Fast Food Pattern and Cardiometabolic Disorders: A Review of Current Studies

Abstract: Background: There are growing concern globally regarding the alarming trend of fast food consumption and its related cardiometabolic outcomes including overweight and obesity. This study aimed to review the current evidences available in relation to adverse effects of fast food pattern on cardiometa­bolic risk factors. Methods: Relevant articles including epidemiological and clinical studies with appropriate design and good quality were obtained through searches of the Medline, PubMed, Scopus databases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
94
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 44 publications
7
94
0
2
Order By: Relevance
“…A review of fast food consumption and cardiometabolic risk indicated that high frequency of fast food consumption was associated with dyslipidaemia. 28 Their results corroborate with our findings as fast foods generally contain processed meats and fried potatoes. Acrylamide, a carcinogen, forms with fried potatoes, because of the availability of carbohydrate, oil and the high temperature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A review of fast food consumption and cardiometabolic risk indicated that high frequency of fast food consumption was associated with dyslipidaemia. 28 Their results corroborate with our findings as fast foods generally contain processed meats and fried potatoes. Acrylamide, a carcinogen, forms with fried potatoes, because of the availability of carbohydrate, oil and the high temperature.…”
Section: Discussionsupporting
confidence: 90%
“…Over three‐quarters of the population reported consuming fried potatoes which was associated with dyslipidaemia as measured by high non‐HDL‐C (>130 mg/dL). A review of fast food consumption and cardiometabolic risk indicated that high frequency of fast food consumption was associated with dyslipidaemia . Their results corroborate with our findings as fast foods generally contain processed meats and fried potatoes.…”
Section: Discussionsupporting
confidence: 89%
“…Data from literature is abundant regarding the association between fast-food consumption and obesity. Research demonstrated that compared to non-consumers individuals that consume fast-food products have a risk of obesity increased by 20-129% (10). Consumption of fast-food products is not only associated with obesity but also with cardiovascular disease, increasing the prevalence of these pathologies with 52-162% (10).…”
Section: Discussionmentioning
confidence: 99%
“…33 This suggests dietary components linked to CVD and stroke (eg, salt, SFA, and TFA) may have greater levels in FFRs than in FSRs. 41 The negative association between diabetes mellitus prevalence and FSRs was also found with respect to obesity 33 and presumably reflects an unaccounted for confounding factor. 33 These cross-sectional correlational data on the association of greater densities of FFRs with both CVD and stroke mortality support other correlational data indicating a link between fastfood consumption and risk factors for CVD.…”
Section: Discussionmentioning
confidence: 90%
“…The energy contents of meals served in FSRs are generally larger than those consumed at FFRs, but they are consumed less frequently, so their contributions to total calorie intake are approximately equal . This suggests dietary components linked to CVD and stroke (eg, salt, SFA, and TFA) may have greater levels in FFRs than in FSRs . The negative association between diabetes mellitus prevalence and FSRs was also found with respect to obesity and presumably reflects an unaccounted for confounding factor …”
Section: Discussionmentioning
confidence: 99%